MODELING OF PROCESSES OF REPAIR OF ENERGY EQUIPMENT - A. Ievlev (Publishing House of the State University of Management, 2017)
In the article the correlation analysis by means of which the author establishes qualitative extent of influence of eleven factors on value of net profit of the enterprise of a power complex is submitted. Use of the modern device of network planning is the cornerstone of approach. The constructed model of network planning allows to choose optimum working hours of the power enterprise at repair and reconstruction of the equipment that in turn will allow to increase efficiency of adoption of administrative decisions.